PENGARUH CELEBRITY ENDORSER, BRAND IMAGE DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK ERIGO DI E-COMMERCE SHOPEE (STUDI KASUS MASYARAKAT KABUPATEN BEKASI) - Cindy Gabriella Gabriella; Basar Maringan Hutauruk (Peneliti.net, 2023)
The purpose of this study is to analyze the influence of Celebrity Endorser, Brand Image and Online Customer Review on the purchase decision of Erigo Products in Shopee E-Commerce. The sampling technique used is purposive sampling, with a sample of 100 respondents. The analysis technique used in this study is quantitative data analysis with SPSS program version 25. Testing of this instrument uses validity and reliability tests. The results of the T (Partial) test show that Online Customer Review (X1) has a positive and significant influence, Brand Image (X2) has a negative and insignificant influence, and Online Customer Review has a positive but not significant influence on the purchase decision of Erigo Products in Shopee E-Commerce. The results of the R Square coefficient of determination show that Online Customer Review, Brand Image and Online Customer Review have an effect of 80.4% on the purchase decision of Erigo Products on Shopee E-Commerce.